The Effect of Lignocellulosic Material and Nanoclay on Physical, Mechanical and Morphological Properties of Wood Plastic Composite - Mohammad Tasoji (Regional Information Center for Science and Technology (RICeST), 2012)
Physical and mechanical properties wood-plastic composites produced from wheat and rice straw particles, nano-clay, polypropylene and MAPP were investigated. The amount of polypropylene and lignocellulosic materials were selected as 60 wt% and 40 wt% respectively. The Nano-clay was added in three levels 0, 2 and 4 wt% and the amount of coupling agent was fixed and set to 2 wt% for all treatments except for the control. The control samples were made from polypropylene and lignocellulosic materials with neither nanoclay nor coupling agent was used. The results showed that the tensile and flexural strengths were decreased by the addition of nanoparticles. For tensile and flexural modulus, adding 2 wt% of nanoclay led to an increase in both moduli. However there was a decrease in both moduli when 4 wt% nanoclay was added. The impact strength decreased adding nanoclay. There was a decrease in 24 hour water absorption when 2 wt% of nanoclay was added but an increase was observed in 4 wt% of nanoclay level. According to the mechanical and physical properties of all the treatments, the samples made of rice straw showed better results compare to wheat straw samples due to their high amount of silica and its compatibility with nanoclay.  SEM test was performed.